2022
DOI: 10.3389/froh.2022.979600
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shift in infection control practices in dental clinics in response to COVID-19 among dental professionals in Thailand

Abstract: Infection control (IC) practice routines depend mainly on knowledge, perception, and awareness of a disease among dental professionals. However, there has been no report on the perception, awareness, and adaptability to the new practice guidelines of Thai dental professionals (dentists, dental nurses, dental assistants, and dental technicians) to the COVID-19 pandemic. This study aims to investigate how dental professionals in Thailand perceive and are aware of COVID-19, and how they have changed their IC prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…During the late stages of the COVID-19 pandemic, a period marked by societal adaptation and a shift toward endemicity, our study revealed that Thai dentists maintained a moderate level of anxiety about contracting COVID-19 from dental treatments, with particularly high anxiety in providing emergency care to high-risk patients. These anxiety levels paralleled those reported during the Delta variant outbreak (11) . Despite the transitional phase, most Thai dentists, especially those involved in AGDP, concurred on the necessity of continuing respiratory infection control measures post-pandemically (7) .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…During the late stages of the COVID-19 pandemic, a period marked by societal adaptation and a shift toward endemicity, our study revealed that Thai dentists maintained a moderate level of anxiety about contracting COVID-19 from dental treatments, with particularly high anxiety in providing emergency care to high-risk patients. These anxiety levels paralleled those reported during the Delta variant outbreak (11) . Despite the transitional phase, most Thai dentists, especially those involved in AGDP, concurred on the necessity of continuing respiratory infection control measures post-pandemically (7) .…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, an intrinsic skewness in this study should be noted, as older dentists composed a small minority of the sample. The sociographic data were collected in the same way as those from a previous study of Thai dentists (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian penelitian terdahulu yang pernah dilakukan di Thailand pada tahun 2021, diperoleh hasil bahwa pada periode pandemi Covid-19 pada periode April 2021 terdapat sebanyak 380 pasien (40,4%) yang mendapatkan pelayanan kegawatdaruratan kesehatan gigi dan mulut pada fasilitas milik pemerintah, sedangkan untuk layanan milik swasta sebanyak 27 pasien dengan proporsinya sebesar 11.4% (7) . Penelitian serupa juga pernah dilakukan sebelumnya dengan menggunakan populasi penelitian seluruh masyarakat di wilayah kerja Puskesmas Lingkar Barat Kota Bengkulu dengan total sampel sebanyak 50 responden menggunakan analisis univariat dan bivariat.…”
Section: Andalas Dental Journalunclassified
“…The Thai ministry of public health has established a minimum of 12 ACH as the recommended standard for the environment in the dental clinic. (47) Air purifiers are highly recommended in dental healthcare facilities to help prevent the spread of infection, not only of COVID-19 but also other respiratory diseases. (14) In addition, this study found that participants were more concerned about oral health problems If dental visits were interrupted due to the spread of coronavirus than contracting COVID-19 from dental work, as evidenced by a statistically significant difference in concern levels.…”
Section: Chapter V Discussionmentioning
confidence: 99%